Fundamental Considerations for Finite Element Modelling of Rubber Material Tensile Test - Abdullah , Muhammad Ahmed (International Journal of Engineering and Management Sciences, 2020)
Aim of this research is to get familiar with the fundamental considerations for finite element modelling of rubber’s tensile test. Hyperelastic materials such as rubber are widely used in a variety of industries ranging from tire to aerospace for various structural applications. The most important feature of rubbers is their ability to experience substantial deformation under small loads and maintain initial configuration without noticeable permanent deformation after removal of the load.